Autonomy and the ambiguity of biological rationalities: systems theory, ADHD and Kant. Issue 2 (4th March 2018) - Haye, Andrés; Matus, Claudia; Cottet, Pablo; Niño, Sebastián
ABSTRACT: We present a theoretical review of notions of autonomy to show how they organize discourses within social sciences around the biological reality of ideal self-regulating individuals. First, we reconstruct key meanings of autonomy in biological theory, focusing on theories of autopoietic systems and their connections to constructivist epistemologies in the social sciences. Second, we discuss developmental and neuropsychological theories of self-regulation, demonstrating conceptual links with biological and systems theory. Third, we discuss the implications for education, using the case of attention deficit hyperactivity disorder as an example on how the construction of the biological, as the natural foundation of individuality, is intensified by the ideal integration of individuals as self-regulated agents. We argue that autonomy, theoretically rooted in modern philosophy, and expanded through system theory to biological and social sciences, has become a biopolitical project contributing to contemporary biological rationalities that produce the educated subject.